DEVELOPING SIMPLE PRESENT TENSE MASTERY IN WRITING DESCRIPTIVE TEXT AT THE FIRST SEMESTER STUDENTS OF STISIP PERSADA BUNDA PEKANBARU - Lia Diana (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2020)
The simple present tense is the most basic tense that should be mastered by the first semester students of STISIP Persada Bunda Pekanbaru. Moreover, descriptive text is one of the text types which use the present tense. Descriptive text is used by the researcher as the text that let the students apply their ability in using the present tense. However, most students still face difficulties in using present tense in writing descriptive text. Thus, the researcher conducted the study entitled "Developing Students Simple Present Tense Mastery in Writing Descriptive Text at The First Semester Students of STISIP Persada Bunda Pekanbaru.” This research aimed to identify the most dominant students' errors and to describe the factors causing students' errors in using present tense in writing descriptive text first semester students of STISIP Persada Bunda Pekanbaru. The study was used mixed methodology as the research method. The population were the first semester students of STISIP Persada Bunda Pekanbaru. In collecting the data, the researcher used the students' writing products in using present tense in writing descriptive text and the questionnaire. The study was showed two points; through the students' writing products would result in the students' errors and the questionnaire would show the factors causing students' errors in using present tense in writing descriptive text. Based on the research findings showed that the most dominant students’ errors were misformation errors with 56 items (62,92%). Moreover, based on the questionnaire could be concluded that the factors causing the students' errors in using the present tense in writing descriptive text were interlingual transfer and intralingual interference.